El discurso anti-supersticioso y contra la adivinación indígena en Hispanoamérica colonial, siglos XVI-XVII - Gerardo Lara Cisneros (Centre de Recherches sur les Mondes Américains, 2012)
This article explores thelegaland theologicalcategoriesthat structured theanti-superstition discourseapplied toindigenous cultures byecclesiastical and civilauthoritiesincolonial Spanish Americain the 16thand 17th centuries.The conquest, evangelization and colonization of Americagave riseto variousdiscourses throughwhichmultiple actorstried toexplain to themselvesthe existenceof the other.One wasthe speechthatcataloged theSpanish Catholicreligioussuperstitionsof the Indians asdemonic(superstition, idolatry, sorcery and divination), these results in acivil and ecclesiasticallawfocused on the extirpation.The fight againstsuperstition wasunderlined by theIndianauthoritiesthroughpastoral visits,diocesanconstitutions, decrees, edicts and manuals to extirpate idolatry,in the catechismsfor Indiansandmanuals forparish priests,and in thecivil and ecclesiastical laws. Thislarge body ofdocumentationshows thatthe fightagainst superstitionof the Indianswas more thana rhetorical discourse, and how it waspositioned in theheart of thetheologicaland legalargumentsthat supportedthe Spanish colonial regimein America.